Development of anticipatory coarticulation of /u/ in typically Malayalam speaking children in the age range of 3-6 years - Litna A. Varghese (Journal of Child Language Acquisition and Development)
Coarticulation is the articulation of two or more speech sounds together, so that one influences the other. Coarticulation is language dependent and can vary from children to adult. Studies in the past have shown that children have more coarticulation than adults; adults have more coarticulation than children; children and adult have similar coarticulatory patterns. Malayalam is a Dravidian language with extra lip rounding feature and also with five place of nasal articulation. The present study investigated the development of anticipatory coarticulation of /u/ in typically developing Malayalam speaking children in the age range of 3-6 years. The data was collected from 60 participants using bisyllabic meaningful words depicted in flashcards. Data were recorded using Sony audio recorder and analyses were done using PRAAT software. Results showed that children did not follow a particular developmental trend, but 4.6-5 years old children showed a different trend compared to children in other age groups.